School Smoking Policies and Health Science Students' Use of Cigarettes, Shisha, and Dipping Tombak in Sudan - Salma El Tayeb El Amin (Frontiers Media S.A., 2019)
The relationship between school smoking policies and students' tobacco use is ambiguous, and little is known about the effect of these policies in low- and middle-income countries. This study was designed to assess the effects of schools' smoking policies and the exposure to residential smoking on cigarette smoking and the use of different kinds of tobacco products by Health Science students. Self-reports of cigarette smoking, use of shisha (smoking of fruits-mixed tobacco using a bowl and a connected hose); dipping tombak (local smokeless tobacco that users usually place inside oral cavity in the groove behind the lower lip), and tobacco use on school premises are analyzed. A cross-sectional survey was carried out using a modified self-report questionnaire, originally developed by WHO, among a representative sample of 1,590 third-year HSS from 25 schools drawn from 13 universities, using a multi-stages sampling technique. The response rate was 100% for schools and 68% for students. A multilevel analysis was performed by nesting student-level in school-level variables. Results from the adjusted models revealed that, when students reported awareness of smoking restriction, they were more likely to be current smokers (OR = 2.91; 95% CI: 1.68-5.02; p = 0.021) and shisha users (OR = 2.17; 95% CI: 1.54-3.06; p = 0.021). Results from additional analysis performed among tobacco users only, showed increased risk of smokers and tombak dippers who smoked or dipped on school premises (OR = 2.38; 95% CI: 1.34-4.25; p = 0.003, OR = 2.60; 95% CI: 1.22-5.56; p = 0.013, respectively). Current smokers (OR = 3.12; 95% CI: 1.98-4.92; p = ≤ 0.001), ever smokers (OR = 1.66; 95% CI: 1.31-2.10; p = ≤ 0.001) and shisha users (OR = 1.73; 95% CI: 1.36-2.21; p = ≤ 0.001) were exposed to residential smoking on one or more days during the previous 7 days. High percentages of those who used any kind of tobacco products reported being aware of school smoking policies, indicating no clear evidence that school smoking policies had an effect on use of any of the mentioned tobacco products. The lack of compliance with school policies shows the need for further policy enforcement and sustainability, taking into account the effect of residential smoking and social influences.